2021
DOI: 10.1186/s12880-021-00719-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric assessment of spleen dimensions and its determinants among individuals living in Arba Minch town, southern Ethiopia

Abstract: Introduction The spleen is a vital lymphoid soft organ that demands constant attention from the clinical point of view. It is a multi-dimensional organ that enlarges in its all dimensions during some disease condition. The detection of the spleen by palpation is not an indicator of an enlarged spleen because normal spleen may be palpable. Therefore, this study aimed to assess the morphometry of spleen dimensions and its determinants among individuals living in Arba Minch town by sonographic exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Solomon et al [ 3 ] studied the length of the spleen by ultrasonography in 708 individuals in Feb 2020 in Arba Minch town, Southern Ethiopia, and found that spleen length increased up to 40 years and decreased thereafter [ 3 ]. Arora et al [ 16 ] examined 160 subjects and calculated splenic length decreases with an increase in age in both males and females.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Solomon et al [ 3 ] studied the length of the spleen by ultrasonography in 708 individuals in Feb 2020 in Arba Minch town, Southern Ethiopia, and found that spleen length increased up to 40 years and decreased thereafter [ 3 ]. Arora et al [ 16 ] examined 160 subjects and calculated splenic length decreases with an increase in age in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The p-value was 0.005 in males and 0.03in females, so it was significant. Solomon et al [ 3 ] his study found that the spleen breadth increased up to 40 years and thereafter decreased. Arora et al [ 16 ] sonographically examined 160 subjects and calculated splenic width decreases with an increase in age in both males and females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations